Evaluation of zinc removal and compressive strength of self-reducing pellets composed of Electric Arc Furnace Dust - Felipe Buboltz Ferreira; Bruno Deves Flores; Eduardo Osório; Antônio Cezar Faria Vilela (REM: International Engineering Journal)
Abstract The amount of Electric Arc Furnace Dust (EAFD) is continuously increasing in mini-mill steel plants. This dust is considered a hazardous waste because of the presence of elements like lead, cadmium and chromium. Among many different treatment processes for this issue, there is the possibility of returning the EAFD back to the Electric Arc Furnace. This article presents a study of the compressive strength of self-reducing cold bonded pellets as well as their zinc removal, in an agglomerate containing EAFD, petroleum coke (PET) and Portland cement. The effects of the reductant and binder employed were discussed. Moreover, an apparatus was built to prevent zinc gas reoxidation inside an electric vertical laboratory furnace. Thus, the fraction of weight loss complemented the result of a previous study indicating the optimal content of PET source usage between 10 to 15%, in mass. Zinc removal and additional X Ray Diffraction outcomes are shown and discussed, concluding that 80% of zinc removal for this system could indicate the possibility of the EAFD reuse.